One Village One Product (OVOP) Assistance Based on Innovation and Digitalization in South Tetebatu Village - Lalu Afandi Gusnanda; Annisa Saputri; Baiq. Oktavia Ningrat; Istiqomah (Saniya Institute, 2025)
This community service project was conducted through the Community Service Program (KKN) of the Sunan Doe Institute of Islamic Studies in Tetebatu Selatan Village, aiming to empower local small and medium enterprises (SMEs) through innovation and digitalization. The program implemented the One Village One Product (OVOP) model as a strategy to strengthen local entrepreneurship and promote sustainable economic development. Using a participatory approach, the project involved direct field observations, interviews, and door-to-door mentoring to identify problems faced by local entrepreneurs, including limited access to production materials, inadequate packaging, and weak digital marketing skills. The program introduced several interventions such as innovative product packaging, training in digital payment systems (QRIS), and social media marketing to enhance business visibility. A notable outcome was the creation of a new local product Brewed Coffee combining traditional coffee and palm sugar. The project succeeded in increasing community engagement, product attractiveness, and market accessibility while fostering student learning through practical community involvement. However, several challenges remained, including inconsistent production schedules and limited resources. Overall, the OVOP-based innovation and digitalization approach demonstrated strong potential for advancing rural entrepreneurship and promoting inclusive economic sustainability in tourist villages.